Evaluation of the Causal Factors and Impact of Contract Change Orders (CCO) on the Implementation of Building Construction Projects - Sukarsih; Yunita Mauliana (Journal of Civil Engineering and Planning (JCEP), 2026)
Contract Change Order (CCO) is a contract change in a construction project where there is additional work to adjust the field volume or schedule changes without changing the contract articles. This study aims to identify the factors causing CCO and evaluate the impact of CCO on the implementation of government building construction projects in West Tulang Bawang Regency using the Influence Diagram method. Based on the results of the analysis that has been done, there are seven main factors that cause CCO, namely: design errors, incomplete drawings, errors in field implementation, errors in implementation methods, weather factors, soil conditions, and price fluctuations. CCO is carried out in 3 ways, namely: revising the design, revising the Cost Budget Plan (RAB), and revising the schedule (S curve). The impacts that occur after the CCO on this project are volume adjustments, time delays, decreased productivity and the potential for conflict. The impact caused by volume adjustments causes changes in material specifications, unit costs and the need for additional work to be done so that it does not change the contract value of the work. The impact caused by the 10-day delay in completion time results in the contractor having to pay a fine of Rp. 280,449,811.50. The impact of quality adjustments can lead to improved specifications, thus improving the quality of work. Another impact of CCO is the potential for conflict, which, if not resolved properly, can escalate to legal proceedings.